Environmental modulation of innate immune gene expression in freshwater and coastal farmed Nile tilapia (Oreochromis niloticus): Environmental effects on immune gene expression in tilapia (Dhaka University Journal of Biological Sciences, 2026)
The expression of immune genes in fish can serve as a biomarker for monitoring disease outbreaks and assessing the impact of environmental stressors. This study investigated the expression of nine innate immune genes in cultured Nile tilapia from freshwater and coastal water aquaculture to understand immune responses to environmental variations. The expression of immune genes was monitored using quantitative RT-PCR. Results showed that IL-1β and viperin were significantly higher in the muscle of freshwater tilapia, while GP1 was higher in coastal tilapia muscle. Conversely, TNF-α, TP4, and Hep2 were significantly lower in coastal tilapia muscle. Metallothionine (MT) expression was significantly higher in the gills of both freshwater and coastal tilapia compared to RAS controls. Between the two culture systems, significant variations occurred in the muscle for IL-1β, TNF-α, GP1, viperin, TP4, Hep1 and Hep2, whereas no significant differences were observed in gills, indicating tissue-specific regulation. Pearson correlation revealed strong positive associations between MT and IL-1β, TNF-α, Hep1 and Hep2 in muscle, as well as between several immune genes in gills. Most immune gene expressions were negatively correlated with water quality parameters, except GP1, which correlated positively with pH. Stocking density showed a positive effect on IL-1β, TNF-α, MT, Hep1 and Hep2. Overall, the findings highlight the influence of environmental factors on tilapia immune responses, emphasizing distinct patterns of inflammatory, antimicrobial, and stress-related gene expression in different aquaculture conditions.Dhaka Univ. J. Biol. Sci. 35(1): 1-16, 2026 (January)